Radiofrequency ablation of a misdiagnosed Brodie's abscess. - Chan, R.; Abdullah, B.; Aik, S.; Tok, C.H. (2011)
Radiofrequency ablation (RFA) therapy is recognised as a safe and effective treatment option for osteoid osteoma. This case report describes a 27-year-old man who underwent computed tomography (CT)-guided percutaneous RFA for a femoral osteoid osteoma, which was diagnosed based on his clinical presentation and CT findings. The patient developed worsening symptoms complicated by osteomyelitis after the procedure. His clinical progression and subsequent MRI findings had led to a revised diagnosis of a Brodie's abscess, which was further supported by the eventual resolution of his symptoms following a combination of antibiotics treatment and surgical irrigations. This case report illustrates the unusual MRI features of osteomyelitis mimicking soft tissue tumours following RFA of a misdiagnosed Brodie's abscess and highlights the importance of a confirmatory histopathological diagnosis for an osteoid osteoma prior to treatment.